Protease activated receptor 2 and matriptase expression in the joints of cats with and without osteoarthritis. Issue 8 (August 2021) - Ariffin, Siti M Zainal; Bennett, David; Ferrell, William R; Lockhart, John C; Dunning, Lynette; Clements, Dylan N; Lascelles, B Duncan X; Ibrahim, Tengku A Tengku; Johnston, Pamela
Objectives: The aim of this study was to determine the presence of protease-activated receptor 2 (PAR2) and matriptase proteins and quantify PAR2 and matriptase mRNA expression in the articular cartilage and synovial membrane of cats with and without osteoarthritis (OA). Methods: A total of 28 articular cartilage samples from adult cats (14 OA and 14 normal), 10 synovial membranes from adult cats (five OA and five normal) and three cartilage samples from 9-week-old fetal cats were used. The presence of PAR2 and matriptase in the cartilage and synovial membrane of the adult samples was detected by immunohistochemical (IHC) staining, while real-time PCR was used for mRNA expression analyses in all samples. Results: PAR2 was detected in all OA and normal articular cartilage and synovial membrane samples but confined to only a few superficial chondrocytes in the normal samples. Matriptase was only detected in OA articular cartilage and synovial membrane samples. PAR2 and matriptase mRNA expression were, however, detected in all cartilage and synovial membrane samples. PAR2 and matriptase mRNA expression levels in OA articular cartilage were five ( P <0.001) and 3.3 ( P <0.001) times higher than that of the healthy group, respectively. There was no significant difference ( P  = 0.05) in the OA synovial membrane PAR2 and matriptase mRNA expression compared with the normal samples. Conclusions and relevance: Detection of PAR2 and matriptase proteins and gene expression in feline articular tissues is a novel and important finding, and supports the hypothesis that serine proteases are involved in the pathogenesis of feline OA. The consistent presence of PAR2 and matriptase protein in the cytoplasm of OA chondrocytes suggests a possible involvement of proteases in cartilage degradation. Further investigations into the PAR2 and matriptase pathobiology could enhance our understanding of the proteolytic cascades in feline OA, which might lead to the development of novel therapeutic strategies.